Cushing’s Syndrome Due To Primary Pigmented Nodular Adrenocortical Disease: –A Case Report Reviews of The Literature– - Choi, Kyung Mook (Korean J Intern Med, 1995)
Primary pigmented nodular adrenocortical disease (PPNAD) is a rare cause of Cushing’s syndrome in infants, children and young adults. It is characterized by non-adrenocorticotropic hormone-dependent hypersecretion of cortisol by multiple, pigmented nodules of hyperplastic adrenocortical cells. Biochemically, PPNAD is characterized by elevated levels of plasma and urinary cortisol that are not suppressed by high doses of dexamethasone (8mg/d for 2 days). Pathologically, the adrenal glands contain multiple dark brown or black nodules and the intervening cortical tissue is atrophic. Recognition of this diagnosis, although rare, is important, as bilateral adrenalectomy is the treatment of choice. We experienced a case of Cushing’s syndrome due to primary pigmented nodular adrenocortical disease and report it with reviews of the literature.